Simulation of Record Arctic Stratospheric Ozone Depletion in 2020 - Grooß, Jens-Uwe; Müller, Rolf (Journal of Geophysical Research: Atmospheres, 2021)
In the Arctic winter/spring of 2019/2020, stratospheric temperatures were exceptionally low until early April and the polar vortex was very stable. As a consequence, significant chemical ozone depletion occurred in the Arctic polar vortex in spring 2020. Here, we present simulations using the Chemical Lagrangian Model of the Stratosphere that address the development of chlorine compounds and ozone in the Arctic stratosphere in 2020. The simulation reproduces relevant observations of ozone and chlorine compounds, as shown by comparisons with data from the Microwave Limb Sounder, Atmospheric Chemistry Experiment-Fourier Transform Spectrometer, balloon-borne ozone sondes, and the Ozone Monitoring Instrument. Although the concentration of chlorine and bromine compounds in the polar stratosphere has decreased by more than 10% compared to peak values around the year 2000, the meteorological conditions in winter/spring 2019/2020 caused unprecedented ozone depletion. The lowest simulated ozone mixing ratio was about 40 ppbv. Because extremely low ozone mixing ratios were reached in the lower polar stratosphere, chlorine deactivation into HCl occurred as is normally observed in the Antarctic polar vortex. The depletion in partial column ozone in the lower stratosphere (potential temperature from 350 to 600 K, corresponding to about 12–24 km) in the vortex core was calculated to reach 143 Dobson Units, which is more than the ozone loss in 2011 and 2016, the years which —until 2020— had seen the largest Arctic ozone depletion on record.